2011
DOI: 10.4137/cin.s7135
|View full text |Cite
|
Sign up to set email alerts
|

Metagenes Associated with Survival in Non-Small Cell Lung Cancer

Abstract: NSCLC (non-small cell lung cancer) comprises about 80% of all lung cancer cases worldwide. Surgery is most effective treatment for patients with early-stage disease. However, 30%–55% of these patients develop recurrence within 5 years. Therefore, markers that can be used to accurately classify early-stage NSCLC patients into different prognostic groups may be helpful in selecting patients who should receive specific therapies.A previously published dataset was used to evaluate gene expression profiles of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Defining the bandwidth of the genomic regulation of neoplasia requires the simultaneous assessment of numerous parameters that circumscribe diverse aspects of tumor biology and facilitate the ‘framing' of clinical behavior [44,45,46]. Numerous successful applications of this principle have advanced the disease management of neoplasia in other sites including breast, liver, colon, prostate and lung cancer [44,47,48,49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…Defining the bandwidth of the genomic regulation of neoplasia requires the simultaneous assessment of numerous parameters that circumscribe diverse aspects of tumor biology and facilitate the ‘framing' of clinical behavior [44,45,46]. Numerous successful applications of this principle have advanced the disease management of neoplasia in other sites including breast, liver, colon, prostate and lung cancer [44,47,48,49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…The detailed analysis of other neoplastic diseases has led to the recognition that evaluation of monoanalyte secretory products (exocytotic or secreted proteins) alone fails to adequately describe the diversity of neoplastic pathobiology ( 56 ). Thus, complex analytic strategies measuring diverse regulators of neoplastic cell biology interfaced with mathematical algorithms to facilitate interpretation have been developed for breast, lung and hematological malignancies ( 57 , 58 , 59 , 60 ). Therefore, a key unmet need that remains is the development of a clinically applicable, multianalyte biomarker that captures NEN behavior and can be used to guide clinical management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study MAGEA10 was found to be one of 3 top genes, which was decisive for 1000 days' survival, and may indicate a better prognosis [22]. With the continuation of the array analysis we found that the MAGEA10 gene was expressed in 26% of Estonia NSCLC patients only, and MAGEA10-derived peptide-specific CTL were reported to be induced from the peripheral blood mononuclear cells in several cohorts [34,35].…”
Section: Discussionmentioning
confidence: 89%
“…The MAGE genes for analysis of gene expression were from a microarray dataset with an initial 85 lung tumor samples and 21 adjacent cancer-free lung samples of non-small cell lung cancer (NSCLC) patients, and the tumor characteristics files, which were previously reported [22]. The MAGE genes' methylation data was retrieved from a dataset of Illumina methylation 450 k chip analysis, but with the same panel of NSCLC samples used in the gene expression array [23].…”
Section: Patients Tumors and Gene Expression And Methylation Microarmentioning
confidence: 99%